Effect of Leverage, Firm Size, and Profitability on Systematic Risk and its Implications on Share Price - Putri Yuniesha Nugrahani; A Mukti Soma; Palti Marulitua Sitorus (Riset Akuntansi dan Bisnis Indonesia, 2025)
Purpose: This study analyzes the effect of leverage, firm size, profitability, and systematic risk on the stock prices of palm oil plantation companies listed on the Indonesia Stock Exchange (IDX) from 2013 to 2023. Research Methodology: This study utilizes panel data and applies three main regression models, namely the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM), to evaluate the impact of the independent variables on stock prices. Results/finding: The study finds that leverage, firm size, profitability, and systematic risk have no significant effect on stock prices, nor does systematic risk mediate the relationship between these variables and stock prices. Conclusions: The study concludes that leverage, firm size, profitability, and systematic risk have no significant effect on stock prices of palm oil plantation companies listed on the IDX during 2013–2023. Systematic risk also does not mediate these relationships, indicating that external factors such as commodity prices, government policies, and macroeconomic conditions play a more dominant role in influencing stock prices in this sector. Limitations: This study is limited to palm oil plantation subsector companies listed on the IDX and the period between 2013 and 2023. External factors, such as macroeconomic conditions, government policies, and environmental factors that might be more significant, have not been deeply analyzed. Contributions: This study contributes to the literature by showing that internal variables such as leverage, Firm Size, and profitability do not always significantly affect stock prices in the context of the palm oil plantation sub-sector in Indonesia.